35.0k views
1 vote
Find f−1(x) for f(x)=9+12x .

1 Answer

5 votes

Answer: f(x)=-2x12x-9

Explanation:

Step1 Interchange the variables. x=−2y+12y−9x

Step2 You then solve for y, y= X/10+9/10

Step3 replace it the y with f, Note when I do this^ I’m using it instead of a -. F^1 (x) = x/10+9/10

Step4 verify that f^1 (x) x/10+9/10 is the inverse of the answer f (x)= -2x+12x-9

User BurgerB
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.